Anthropos into humanitas: Civilizing violence, scientific forestry, and the 'Dorobo question' in eastern Africa. (August 2017) - Cavanagh, Connor J
Early interactions between state administrators and forest-dwelling communities in eastern Africa yield significant insight into colonial attempts to grapple with difference across hierarchically conceptualized 'races', classes, tribes, and radically alternative livelihoods. In particular, uncertainties related to the governance of forest-dwellers resulted in a problematic known as the 'Dorobo question' in Kenya Colony, the former word being a corruption of the Maasai term for the poor, the sinful – and hence – the cattle-less. Drawing upon archival research in Kenya and the United Kingdom, I argue that halting attempts to govern such communities illuminate an historically and geographically specific dimension of late imperial Britain's apparently 'liberal' biopolitics, which entailed not the 'abandonment' of populations, per se, but rather the elimination and subsequent transformation of livelihoods, ontologies, and sustainablities perceived as fiscally barren or otherwise of little use to the colonial state. Far from being resolved, however, the afterlives of these logics of elimination highlight the stakes of contemporary struggles over eastern African forests, and particularly so in the context of an emergent transition to ostensibly 'green' forms of capitalism in the region.